Social support and work-family conflict amongst low-income workers in South Africa: the relationship between social support and work-family conflict amongst low-income workers in South Africa - Walters, Alexandra (Organisational Psychology, 2026)
Although most workers are challenged by competing work and family demands, lowincome workers are under-represented in work-family research. Work-family conflict (WFC) dynamics differ for low-income workers, who generally differ in access and resources available to higher-wage workers inside and outside of the workplace. Little is known about the support resources low-income workers draw on to manage WFC. Without formal organisational support, low-income workers tend to rely on interpersonal relationships in the workplace, family and community; the latter have attracted little research attention. The prevailing understanding, rooted in resource-based stress theory, is that support has a direct ameliorative effect on WFC. This study investigates the direct and interactive predictive effect of collegial, organisational, family, and community support on the WFC of low-income workers. It also examines how organisational support for family mediates the effect of supervisor support on WFC. Data was collected using a quantitative, descriptive, cross-sectional research design using self-report questionnaires. Participants were front-line, low-income workers in cleaning, catering, and security functions employed across multiple sites at a large outsourcing company (N= 339). The study aims to gain a deeper understanding of the WFC experiences of low-income workers, a group that has been underrepresented in research. By focusing on this demographic within a specific organisational context in South Africa, the study aims to uncover the unique challenges front-line, low-income employees face in balancing work and family responsibilities. The differential experiences of support among low-income workers highlights the need to understand the effect and interaction of different sources of support. Research results indicate that collegial support has a significant negative relationship with work-to-family and family-to-work conflict, while organisational support for family had a significant negative relationship with family-to-work conflict and not work-to-family conflict. However, community and family support were not seen to have a significant relationship with WFC. The results on the mediating effect of organisational support for the family were not significant. The implications for these findings are discussed.